Rheumatic diseases in women: impact on pregnancy and neonatal health - N. A. Pekareva (Лечащий Врач)
Background. Rheumatic diseases are a large group of heterogeneous inflammatory and degenerative-metabolic diseases, characterized by systemic damage, covering all structures of connective tissue (joints, cartilage, bones, periarticular tissues), and also involve blood vessels, internal organs, skin and mucous membranes, mainly with a systemic, not local, nature of damage. Most chronic rheumatic diseases occur in women, and the onset coincides with the peak of childbearing age (18-45 years). The number of women with rheumatic diseases planning to have children increases annually everywhere.Results. The study of pregnancy outcomes, children's health in the neonatal period and during follow-up observation was conducted in women with rheumatic diseases. Women with rheumatic diseases are more likely to have premature births or require operative delivery. Newborns have an increased frequency of pathologies, including prematurity, low gestational weight, intrauterine pneumonia, necrotizing enterocolitis, respiratory distress syndrome and cardiac arrhythmias such as bradycardia and atrioventricular blocks. Children born to women with rheumatic diseases have lower weight-for-height indicators and Apgar scores, as well as a high frequency of complications in the early neonatal period. The health of children at 1 year of life was characterized by the presence of predominantly functional disorders. The decision on breastfeeding should be made individually for each woman with rheumatic diseases.Conclusion. Women with rheumatic diseases planning pregnancy require comprehensive dynamic observation. It is critical to adapt the therapeutic strategy to control rheumatic diseases and minimize the impact of autoantibodies on the fetus.